A phase III randomized controlled study on the efficacy and improved bowel function of prolonged‐release (PR) oxycodone‐naloxone (up to 160/80 mg daily) vs oxycodone PR. (22nd June 2017) - Dupoiron, D.; Stachowiak, A.; Loewenstein, O.; Ellery, A.; Kremers, W.; Bosse, B.; Hopp, M.
Abstract: Background: Oxycodone/naloxone (OXN PR) is a prolonged‐release formulation containing oxycodone and naloxone in a 2:1 ratio. This study aimed to evaluate the tolerability and efficacy of doses up to OXN160/80 mg PR compared with oxycodone prolonged‐release formulation (OxyPR) in a randomised controlled trial. Methods: Two hundred and forty‐three patients were randomised to treatment with OXN PR ( n =  123) or OxyPR ( n =  120) during the 5‐week double‐blind study. Measured were: opioid‐induced constipation [bowel function index score (BFI)]; analgesic efficacy (NRS 0–10); daily laxative rescue medication use; rescue medication use, and the number of complete spontaneous bowel movements (CSBMs) per week. A subanalysis was conducted in cancer patients. Results: Greater reductions in mean BFI scores were reported for the OXN PR group compared with OxyPR from Week 1 onwards; at Week 5 the mean change from baseline was −32.5 versus −14.2. Average 24‐h pain scores were low and remained stable in the range 3–4 in both treatment groups. Analgesic rescue medication use was similar between the groups. Patients receiving OXN PR used significantly lower mean daily doses of laxative rescue medication than those receiving OxyPR ( P  =   0.006). The number of CSBM in the OXN PR group approximately doubled compared with a 25% decrease in the OxyPR group. Comparable results to the total study population were reported in the cancer patient subgroup. Conclusions: OXN PR in daily doses of up to 160/80 mg significantly improves bowel function compared with equivalent doses of OxyPR while still providing comparable analgesic efficacy. Significance: Effective analgesia can be achieved using oxycodone/naloxone PR up to 160/80 mg daily without compromising bowel function. A similar outcome was reported in cancer and non‐cancer patients.